Digital Literacy Analysis through Flipped Classroom Learning using Web-Edmodo on Buffer Solution Material - Setyorini, Triyana Wahyu; Paristiowati, Maria; Afrizal, Afrizal (International Journal of Social and Management Studies, 2023)
- This study aims to determine students' digital literacy through Flipped Classroom learning on buffer solution material using web-Edmodo. The research was conducted at SMA N 1 Padangan, East Java. This research method is a qualitative method. The learning model used is the flipped classroom, while the Edmodo web is a platform that can be used in the teaching and learning process anywhere and anytime. Data collection techniques include distributing digital literacy questionnaires, observation, interviews, reflective journals, and documentation. The digital literacy dimensions analyzed in this study consist of information, communication, content-creation, safety, and problem-solving. The results showed that the students had a very good category in the dimensions of information, communication, content creation, and safety, while in problem-solving they had a good category. Thus it can be concluded that the use of the Edmodo web in buffer solution learning through the flipped classroom can foster students' digital literacy